Pengaruh Self Esteem, Empowerment, dan Team Work Terhadap Kepuasan Kerja Karyawan Pada PT. BPR TISH di Gianyar - Ni Luh Adisti Abiyoga Wulandari; Ni Komang Sumadi; Ni Nyoman Adityarini Abiyoga Vena Swara (UNHI Press, 2020)
Job satisfaction is an employee's feelings about his work, whether happy/like or not/disliked as a result of employee interaction with his work environment or as a result of employee assessment of his work. The formulation of this research problem is how the partial and simultaneous influence of self esteem, empowerment and teamwork on job satisfaction of employees of PT. BPR Tish in Gianyar. The purpose of this study was to determine the partial and simultaneous influence of self esteem, empowerment and teamwork on job satisfaction of employees of PT. BPR Tish in Gianyar. This research was conducted at PT. BPR Tish in Gianyar with a total sample of 39 peoples. Data collection methods used were observation, interviews, documentation, literature and questionnaires. While the data analysis techniques are validity, reliability, classic assumption test, multiple linear regression analysis, correlation and determination analysis, t test, and F test. The test results show that there is a positive and significant effect of partially self esteem on job satisfaction where values ​​are obtained Regression coefficient b1 is 0.434 and the calculated t1 value is 2.180 greater than the t-table of 1.697 with a sig value of 0.018. There is a positive and significant effect of partial empowerment on job satisfaction where the regression coefficient b2 is 0.302 and the t2-count is 3.402, greater than t-table 1.697 with a sig 0.002. There is a positive and significant effect of teamwork partially on job satisfaction where a regression coefficient of b3 is 0.309 and a t3-count of 2.194 is greater than t-table of 1.697 and a sig of 0.020. There is a positive and significant effect of self-esteem, empowerment and teamwork simultaneously on employee job satisfaction at BPR Tish in Gianyar. When seen from the results of the F-test obtained F1-count is 39.889 greater than the F-table of 2.92 and a sig value of 0,000. Based on this, PT. BPR Tish in Gianyar provides an opportunity for employees to show their abilities and competencies, give recognition and respect for their abilities and encourage the spirit of collaboration in work teams so as to create satisfaction for the work they do because what they do is successful and creates optimal results.